Asimmetrija lateral'nych myšecnych grupp kak faktor organizacii perekrestnych dviženij v lyžnych lokomocija - Dorozhko, A. S.; Guseynov, D. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article is devoted to the problem of motor asymmetry of lateral muscle groups when performing sports movements. The quantitative approach to recording and assessing the symmetry of the development of muscle strength abilities using electronic dynamometry is reflected. The data on the strength preparedness of biathlete athletes are presented based on which it is proposed to carry out a quantitative assessment of motor asymmetry. The necessity of correcting the training process taking into account individual asymmetry profiles on the example of skiing locomotion is substantiated.